2003
DOI: 10.1016/s1097-2765(03)00486-6
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Phosphoinositide Phosphatase, MTMR2

Abstract: Myotubularin-related proteins are a large subfamily of protein tyrosine phosphatases (PTPs) that dephosphorylate D3-phosphorylated inositol lipids. Mutations in members of the myotubularin family cause the human neuromuscular disorders myotubular myopathy and type 4B Charcot-Marie-Tooth syndrome. The crystal structure of a representative member of this family, MTMR2, reveals a phosphatase domain that is structurally unique among PTPs. A series of mutants are described that exhibit altered enzymatic activity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(85 citation statements)
references
References 66 publications
(2 reference statements)
2
83
0
Order By: Relevance
“…Domains in pleckstrin were initially identified as a family of homologues ~100‐120 aa,29 and several structures were solved soon after 15. GRAM domains were identified as a family of sequences ~70 aa long,30 with the first solved structure identified as beta sheets 1–5 of a complete PH‐like domain 18…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Domains in pleckstrin were initially identified as a family of homologues ~100‐120 aa,29 and several structures were solved soon after 15. GRAM domains were identified as a family of sequences ~70 aa long,30 with the first solved structure identified as beta sheets 1–5 of a complete PH‐like domain 18…”
Section: Resultsmentioning
confidence: 99%
“…Hence, prediction of new PH‐like domains may identify residues that are functionally important for intracellular traffic. Since the initial discovery of classical PH domains, newly solved PH‐like structures have unexpectedly been found, both early on,17 and at least 10 times since 18, 19, 20, 21, 22, 23, 24, 25, 26, 27. Each of these discoveries added a new family of PH‐like domains to a growing PH‐like clan 28.…”
Section: Introductionmentioning
confidence: 99%
“…According to Matthews coefficient calculations with the molecular weight of 64 kDa, the crystallographic structure might contain ten to 22 protein molecules in the asymmetric unit with a V M of 2.13-4.68 Å 3 Da À1 and a solvent content of 42.2-73.7% (Matthews, 1968). Molecular replacement (MR) was performed using the crystal structure of human MTMR2 (PDB entry 1lw3; 37% sequence identity; Begley et al, 2003) or MTMR6 (PDB entry 2yf0; 34% sequence identity; Structural Genomics Consortium, unpublished work) as a search model. As the relative positions of the PH-GRAM domain and the phosphatase domain are different in the two MTMR structures, each domain was also used as a search model for MR.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that MTMR3 plays a critical role in regulating autophagy and cancer cell migration, suggesting MTMR3 may be a novel therapeutic target in metastatic cancer (Oppelt et al, 2013(Oppelt et al, , 2014Taguchi-Atarashi et al, 2010). Structural studies of MTMR2 revealed that the phosphatase domain is structurally unique among PTPs, providing the substrate specificity, and the PH-GRAM domain is a larger motif with a PH domain fold, which is known as a phosphoinositide-binding module (Begley et al, 2003(Begley et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Derivatives with shorter alkyl chains such as butanoyl ester side chains have been developed and applied to protein cocrystallisation studies. [15] However, these compounds have also been reported to be unstable. Cocrystals of known PIPbinding proteins with the equivalent lipid-free inositol phosphate, such as myo-inositol 1,4,5-trisphosphate (IP3), have also been prepared but these analogues completely lack the diacylglycerol lipid moiety that is likely to contribute to the affinity of these compounds with certain proteins.…”
Section: Introductionmentioning
confidence: 99%